Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages HOUSING The most serious and urgent domestic problem facing the Labour Government in July, 1945, was housing, and after one year of power the situation is still grave. The provision of homes for the people is a task which must be accomplished. It is not only a question of terrible living conditions, but of countless human tragedies, broken marriages, declining health, fear and worry, disillusionment and embitterment. If ever a governmental task had to be thought of in terms of human need, then that is the position with housing to-day. The difficulties facing the Labour Government were, of course, tremendous. The muddle and confusion of the Coalition (for which, however, Labour must accept some responsibility), the havoc caused by Jerry bombers and jerry-builders, shortage of materials and labour, ineffective control over the first essential of land, these were only some of the inherited difficulties. There was only one way of meeting the situation, the application of full socialism, involving the common ownership of the land, the building industry and the materials industries, the replacing of the profit motive with the incentive of service, and a financial plan excluding interest. The Labour Party, however, did not fight the General Election with such a programme, which would have cut at the very roots of the old order, involving as it does so many issues of vital importance to the capitalist class. Thus, the explanation of the Labour Government's failure to overcome the housing crisis is the fundamental truth that it is a reformist government, compromising with capitalism, and incapable of meeting the challenge of a developing world with the principles and policy of socialism. After one year of power, the acquisition of land for building is still a long drawn-out affair. The April, 1946, legislation reads better on paper than it is in practice, for although in theory a local authority can enter land after 14 days notice, with compensation to be decided later, in actual practice owners are making use of the weakness in the legislation which makes an enquiry necessary if there is public opposition to the acquisition. In a society of class barriers, nothing is simpler than to stimulate opposition to the erection of what are sneeringly called "council 16 15X/2/98/21